Who's afraid of designer babies? - Manzies, Stuart; Cousins, Sean; Wright, Tony; Film Australia (Princeton, N.J. : Films Media Group, 2006)
Pre-implantation genetic diagnosis (PGD) allows doctors and parents to screen brand-new embryos for genetic diseases. Interviews with bioethics experts, including Oxford professor Julian Savulescu and Dr. Francis Fukuyama of Johns Hopkins University, elucidate both sides of the debate
Title from title screen
Films Media Group: Films for the Humanities & Sciences, Cambridge Educational, Meridian Education, Shopware
DVD format
Keywords: Genetic engineering -- Australia; Genetic engineering -- Moral and ethical aspects; Fertilization in vitro, Human -- Australia -- New South Wales; Human reproductive technology -- Australia -- New South Wales; Human reproductive technology -- Moral and ethical aspects; Human genetics -- Moral and ethical aspects